Is Newtonian gravitational constant a quantized constant of microscopic quantum gravity? - Seshavatharam, UVS; Lakshminarayana, S (International Journal of Advanced Astronomy, 2020)
Considering the Newtonian gravitational constant as a quantized constant of microscopic quantum gravity, an attempt is made to fit its value in a verifiable approach with reference to three large atomic gravitational constants pertaining to weak, strong and electromagnetic interactions linked with a quantum relation. Estimated value seems to be 865 ppm higher than the recommended value.Â Â